Comparison between intratympanic injection of dexamethasone and methylprednisolone in idiopathic sudden sensorineural hearing loss: A randomized clinical trial - Kourosh Eftekharian; Elnaz Najafi; Maryam Amizadeh; Noosheen Mokari; Mohammad Faramarzi; Yalda Izadparast; Yalda Jabbari Moghadam; Ali Eftekharian (Laryngoscope Investigative Otolaryngology)
Abstract Objective To compare the hearing outcomes of patients with idiopathic sudden sensorineural hearing loss after intratympanic (IT) injection of methylprednisolone and dexamethasone. Study design Randomized case‐controlled clinical trial. Methods Seventy‐five patients diagnosed with idiopathic sensorineural hearing loss were randomly divided into two groups based on therapy. Both groups received oral prednisolone (10 mg/kg; maximum of 60 mg) for 10 days without tapering and received IT injections two times a week for 2 weeks (four injections in total). One group received an IT injection of a 40 mg/mL solution of methylprednisolone, and the other one, 4 mg/mL dexamethasone. Three comparisons between the initial and third‐month hearing tests were made to assess the degree of hearing change: (1) pure tone improvement in each individual tone (0.5, 1, 2, 3, and 4 kHz); (2) word‐recognition score improvement; and (3) complete, partial, and no recovery of hearing calculated (as defined by American Academy of Otolaryngology‐Head and Neck Surgery Clinical Practice Guidelines). Results The study was completed with 69 of the 75 patients—34 in the methylprednisolone group and 35 in the dexamethasone group. The groups' differences in frequency‐specific hearing improvement were not statistically significant. There was no statistically significant difference in the word recognition score improvement between the two groups. Additionally, there was no discernible difference between the two groups' hearing recovery rates. Conclusion Methylprednisolone and dexamethasone IT injection therapy had similar hearing outcomes. Level of evidence 2.